Uji Aktivitas Antijamur Bacillus spp. Terhadap Colletrotrichum scovilei Penyebab Antraknosa Cabai Rawit - I Wayan Diksa Gargita; Khamdan Khalimi (Agriculture Faculty of Flores University, 2023)
Anthracnose caused by the Colletotrichum scovillei is main diseases of cayenne pepper (Capsicum frutescens L.) that affect on plant productivity. The control of plant diseases caused by pathogenic fungi has been widely reported by utilizing of biological agents that applied in biofungicides. Bacillus spp. was reported to have antagonistic abilities against several pathogenic fungus. The purpose of this study was to determine the antagonistic ability of several Bacillus species against Colletotrichum scovillei. The begins was rejuvenatio of the C. scovillei and B. subtillis, B. cereus, B. coagulans, B. thuringiensis that have been identified. The inhibition of Bacillus spp. on the growth and biomass of C. scovillei was tested in vitro, as well as testing the inhibition of Bacillus spp. filtrates on C. scovillei colonies. The inhibitions of Bacillus spp. against the growth of C. Scovillei were ranged from 91.36% to 96.46% and a percentage inhibition on biomass of C. scovillei were ranged from 85.35% to 88.53% compared to the control. Bacillus spp. filtrates was tested at concentrations of 20%-90% were able to inhibit the growth of C. scovillei colonies with a percentage inhibition up to 99.84%. The good quality standard of biological agent must have >70% of inhibition in vitro. The inhibition that occurs by Bacillus spp. on the growth of C. scovillei is likely due to competition for nutrient and space. And other, the possibility of an antagonistic mechanism in the form of the presence of chitinase, which is one of the antifungal metabolite compounds.